2019
DOI: 10.1159/000503748
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characteristics and Endoscopic Management of Gastric Premalignant Lesions in France

Abstract: Introduction: Surveillance of gastric precancerous lesions (GPL) is recommended, but the data on their clinical and endoscopic management in a "real-life" practice are limited. Our aim was to study the modalities of endoscopic management of patients with GPL in France. Design: All the patients diagnosed with GPL in our center between 2000 and 2015 were grouped and analyzed according to the most severe GPL found, in the following order: atrophic gastritis only (AG), intestinal metaplasia (IM), low grade dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…3,4 Each of these lesions is associated with an increased risk of GC which correlates with the severity of the lesions, 5,6 but AG and IM are the most common and the most widely studied. [7][8][9] The recent guidelines provide recommendations for the management of patients harboring GPL, 10,11 with the aim to diagnose patients with early and curable neoplasia. However, the precise evolution of GPL is not completely understood and the surveillance of the patients known to be at risk for GC remains challenging.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 Each of these lesions is associated with an increased risk of GC which correlates with the severity of the lesions, 5,6 but AG and IM are the most common and the most widely studied. [7][8][9] The recent guidelines provide recommendations for the management of patients harboring GPL, 10,11 with the aim to diagnose patients with early and curable neoplasia. However, the precise evolution of GPL is not completely understood and the surveillance of the patients known to be at risk for GC remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that the correlation between endoscopic evaluation of the mucosa and histologic findings is very poor. 7 Besides, histology-based diagnosis is subjected to a sampling error because of an often uneven distribution of GPL within the stomach mucosa. In this setting, several strategies have been developed to increase the patients' adhesion to surveillance and to improve targeting of the patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 EoE is also detected in 1-8% of symptomatic patients undergoing endoscopy, 37 whereas, for instance, comparable recent features of H. pylori infection are higher (41-63.67%). 74,75 Moreover, the current prevalence of H. pylori infection in Asia is: Central Asia 79.5%, South Asia 28.6-81%, and Western Asia 49.1-77.2%. 76 Additionally, owing to immigration, H. pylori infection prevalence in Western countries is high.…”
Section: H Pylori and Eoe: Illuminating The Gapmentioning
confidence: 99%